Peranan Intellectual Capital Pada Intermediary Function Terhadap Return On Equity Perusahaan Perbankan - Anita Permatasari (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2019)
This study aims to examine the role of Intellectual Capital in banking companies listed on the Indonesia Stock Exchange. The research data used are secondary data in the form of financial data and financial ratios of banks listed on the Indonesia Stock Exchange from 2010 to 2016 using the purposive sampling method. Based on sampling criteria, 23 banks were selected and divided into two categories: banks with low Intellectual Capital and banks with high Intellectual Capital. The results showed that there were three findings, namely the first test results on banks with low Intellectual Capital and high Intellectual Capital showed that Non Performing Loans (NPL), Operational Costs Per Operating Income (BOPO), Loan to Deposit Ratio (LDR), and Capital Adequacy Ratio (CAR) does not affect Return on Equity (ROE). Second, the results of testing on banks with low Intellectual Capital and high Intellectual Capital indicate that Non Performing Loans (NPL), Loan to Deposit Ratio (LDR), and Capital Adequacy Ratio (CAR) have no effect on Return on Equity (ROE). Third, the results of testing on banks with high Intellectual Capital indicate that Operational Cost Per Operational Income (BOPO) has an effect on Return on Equity (ROE).